2020
DOI: 10.1007/s10660-020-09434-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction on transaction amounts of China’s CBEC with improved GM (1, 1) models based on the principle of new information priority

Abstract: Benefited by e-commerce activities and information technology development, cross-border e-commerce (CBEC) has experienced rapid growth and attracted much research attention. This study takes China’s CBEC as a typical research object and intends to forecast its future development trend based on an exploration of its dynamic changing rules as a whole. The data set of transaction amounts of China’s CBEC from 2008 to 2018 was used in the modeling processes of improved grey models (GM) (1,1) proposed in this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…China's B&R project aims to support trade co-operation among various countries, including Asian, African, and European countries. In particular, under the B&R initiative, the Chinese government has introduced many promotion policies to enhance the development of CBEC to promote trade with B&R countries [4]. Mou et al [31], Li et al [32], and Wang et al [33] also emphasized that the B&R initiative promotes the development of CBEC and provides more opportunities for Chinese firms to export their products and services to overseas markets.…”
Section: Cbec and International Tradementioning
confidence: 99%
See 2 more Smart Citations
“…China's B&R project aims to support trade co-operation among various countries, including Asian, African, and European countries. In particular, under the B&R initiative, the Chinese government has introduced many promotion policies to enhance the development of CBEC to promote trade with B&R countries [4]. Mou et al [31], Li et al [32], and Wang et al [33] also emphasized that the B&R initiative promotes the development of CBEC and provides more opportunities for Chinese firms to export their products and services to overseas markets.…”
Section: Cbec and International Tradementioning
confidence: 99%
“…These policies include the development of online payments, e-commerce platforms, logistics, customs clearance services, and tariff incentives [45]. For example, Mi et al [4] and Miao et al [46] pointed out that CBEC is an important factor in the B&R initiative, and preferential CBEC policies such as tax refunds and exemption policies launched by the State Taxation Administration have encouraged the Chinese enterprises to export their products to overseas markets. Wang et al [8] found that with the implementation of the B&R initiative, CBEC can offset the negative impact of transportation costs by improving logistics, thus, promoting total international trade volumes.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prediction model of Mi et al (2021) predicts China's CBEC industry will continually have stable growth. The regression model established by Peng (2021) discloses a nearly one-to-one association between CBEC trade volume to international trade volume for China.…”
Section: Market Driven Value Creationmentioning
confidence: 99%
“…Zhengzhou Airport Economic Zone the China's first smart city proven its success through a smart logistics model using a combination of artificial intelligence technology and big data analytics (Guan, 2021). Mi et al (2021) shows the importance of a stable information technology system in overcoming unprecedented dynamic environment change in a timely manner, materialising market penetration instantly.…”
Section: Digitally Drive Business Transformationmentioning
confidence: 99%